1984
DOI: 10.1113/jphysiol.1984.sp015129
|View full text |Cite
|
Sign up to set email alerts
|

Cooling dissociates glucose‐induced insulin release from electrical activity and cation fluxes in rodent pancreatic islets.

Abstract: SUMMARY1. Insulin release and fl-cell membrane potentials in response to glucose at 37 and 27 TC have been measured simultaneously in single, micro-dissected, perifused islets of Langerhans from normal mice.2. Insulin release and 45Ca outflow in response to glucose at 37 and 27 'C have been measured simultaneously from perifused islets isolated by collagenase digestion from normal rats.3. The effect of cooling on fl-cell membrane potassium permeability was assessed by changes in measured membrane potential and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
23
1

Year Published

1986
1986
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 28 publications
8
23
1
Order By: Relevance
“…5 ng/100 spheroids per hour respectively. This is consistent with inhibition of glucose-induced insulin release by cooling (Atwater et al 1984). These findings demonstrate de novo synthesis and processing of insulin and physiologically regulated secretion.…”
Section: Resultssupporting
confidence: 74%
“…5 ng/100 spheroids per hour respectively. This is consistent with inhibition of glucose-induced insulin release by cooling (Atwater et al 1984). These findings demonstrate de novo synthesis and processing of insulin and physiologically regulated secretion.…”
Section: Resultssupporting
confidence: 74%
“…Although these changes may be due to the nonspecific effects of cooling, they would also, in fact, be expected if cooling inhibited K ATP channel opening after the suppression of insulin secretion within the islet. We have quantitatively tested this hypothesis using a computer simulation in which the effect of cooling was modeled as an 8% reduction in maximal K ATP conductance (R. Bertram and A. Sherman, unpublished observations) and found that indeed this resulted in qualitatively similar changes in bursting to those reported by Atwater et al (46) and Debuyser et al (47). Although this does not prove our hypothesis that secreted insulin activates K ATP channels in mouse islets, these classic temperature experiments do not rule out the hypothesis.…”
Section: Discussionmentioning
confidence: 79%
“…A general objection to the hypothesis that secreted insulin functionally modulates glucose-induced bursting via K ATP channel activation is the observation that inhibiting islet insulin secretion by cooling islets from 37 to 20 -27°C does not abolish glucose-induced bursting (46,47). This suggests that secreted insulin must therefore not be required for islet bursting to occur.…”
Section: Discussionmentioning
confidence: 99%
“…2A. This change, however, is more "normal" (32) in that normal bursting can be recovered by a small increase in rin (e.g., from 20 ms to 20.7 ms). This is caused by a shift in the Hopf bifurcation point on the upper branch, whose location is sensitive to both GATP and T, Larger values of Tn.-e.g., 22 ms-shift the Hopf bifurcation curve so far to the left that only the "beating" type spiking is observed.…”
Section: Modification Of Ca2+ Currents and Normal Burstingmentioning
confidence: 99%